(untitled) (Research, Society and Development, 2021)
Objective: The objective of this work is to present a clinical case of endodontic treatment in a tooth with incomplete rhizogenesis and pulp necrosis through the apexification technique, using intracanal medication with calcium hydroxide during 1 year of treatment, obtaining favorable results. Methodology: Based on the patient’s permission through the Free and Informed Consent Form to share her image for the proper purpose, this study is a clinical case report of descriptive analytical nature (Pereira et al., 2018). Case report: Patient L.V., female, 08 years old, leucoderma, attended at the faculty’s dental clinic (Fametro), accompanied by her guardian. In the anamnesis, the patient’s mother reported that her daughter had suffered a fall from her own height, fracturing the maxillary central incisor with pulp exposure. Complementary radiographic examination revealed a periradicular lesion of endodontic origin in element 11 and 12, incomplete root formation with an open foramen in stage 8 of Nolla. Vertical percussion was performed with a clinical mirror indicating a positive response, pulp necrosis and element 11 had grade II mobility. Final Considerations: In view of the clinical case report presented, it was possible to observe the importance of endodontic therapy for the preservation and maintenance of the dental element with incomplete rhizogenesis and pulp necrosis, however, the apexification therapy, with calcium hydroxide used for decades, took the resolution of symptoms, repair of the tissues involved and induced apical closure acting positively in the disinfection of the root canal.